IMPACTS-Hamilton: A GIS-Based Decision-Support Tool for Evaluating the Transportation-Related Impacts of an Aging Population - Pavlos Kanaroglou; D.M. Scott; A. Paez; K.B. Newbold; H.F. Maoh (European Regional Science Association (ERSA), 2006)
As in other developed countries, Canada's population is aging. In fact, by 2026, approximately 21% of Canadians will be at least 65 years old – an increase of almost 9% from 2001. In absolute terms, the elderly population is expected to grow from 3.935 mi
Keywords: 330